Proposed Package Distribution Routes at PT. Pos Indonesia Mail Processing Center Bandung - Martikasari, Arida Murti; Yulianto, Irwan (Universitas Insan Cendekia Mandiri, 2024)
Pos Indonesia is a delivery service provider company that has a central distribution center in theregion of West Java, which is the Mail Processing Center Bandung. MPC Bandung has a function to regulatethe distribution of packages according to the destination area. The company has a target to minimizetransportation costs when shipping goods. The delivery process carried out by MPC Bandung can bemodeled as the Vehicle Routing Problem (VRP). This research focuses on the efficiency of the distributionroutes of documents and packages to 12 destination post offices in the secondary West Java Region. Analysiswas conducted using two classical heuristic methods, Clarke and Wright Savings and Nearest Neighbor, withthe aim of obtaining a more optimal route in order to minimize transportation costs. Alternative 2, which isdesigned using the CAWSA method, was chosen to be the best alternative because it produces the shortestmileage output of 894.2 km per day with a savings of 54.11% on the existing route, which has a total mileageof 1,948.7 km. This alternative was chosen as a proposed route improvement for the company. Thetransportation cost efficiency was obtained at 50.94% from Rp. 115.546.200 for the existing route to Rp.56,686,500 for the selected route.